(untitled) (Western European Journal of Modern Experiments and Scientific Methods, 2024)
The main task of environmental education in primary schools is to foster a rational and responsible attitude to the natural environment, which is based on the basis of environmental awareness. In this article highlights of effective use of the ”Brain storming” method in the formation of environmental thinking of primary school students